Effects of Slaughter Weights on Meat Yield and Chevon Characteristics of West African Dwarf Goat (bucks) - Ayanniyi, N. N.; Olusola, O. O.; Kenneth-Obosi, O.; Adeyemi, S. A.; Umar, A.; Eze, J. N.; Orimogunje, A. D. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2022)
The study was conducted at the Ruminants section of the Teaching and Research Farm of the University of Ibadan, Ibadan to evaluate the effects of slaughtering weights on the meat yield and other chevon characteristics of West African Dwarf bucks (WAD). Fifteen WAD bucks were fed similar diets before sacrificing nine at three pre-determined weights of 15, 20 and 25kg to evaluate relative percentage proportions of Eviscerated Weight-EW, Hot Carcass Weight-HCW, Dressing percentage-DP, Rib Eye Area-REA, Meat to Bone Ratio-MBR and Total Fat Deposit-TFD in a Completely Randomised Design (CRD). Also evaluated were the physicochemical characteristics of each of the carcasses relative to the pre-determined weights. The results showed that the EW ranged from 62.0% in 15kg-bucks to 71.8% in 25kg-bucks, while HCW ranged from 52.1% in 15kg-bucks to 55.3% in 25kg-bucks. The 25kg-bucks had the highest TFD of 4.7±0.3% compared with 3.1±0.1% and 4.4±0.4% in 15 and 20kg-bucks, respectively. Bucks with higher weights elicited more REA as compared with those with lower weights. However, there was an inverse relationship between ether extract and the crude protein as the weights of the bucks increased. The DP was not significantly different among the treatments. In conclusion, the higher weights observed in the bucks were not necessarily in terms of meat value but only in terms of fat. This goes to show that when an animal has reached its full maturity, it doesn’t add more meat but rather it accumulates fat.